ДОСЛІДЖЕННЯ ПОРОГОВИХ ХАРАКТЕРИСТИК ЗОРУ ПРИ ВИКОРИСТАННІ ОСВІТЛЮВАЛЬНИХ УСТАНОВОК З РІЗНИМИ ТИПАМИ ДЖЕРЕЛ СВІТЛА - Таряник, М.М.; Сіробаба, О.О.; Овчинников, С.С. (Інститут електродинаміки НАН України, Київ, 2011)
Threshold values of illumination produced by different sources under illumination fluctuation and visual processes under superthreshold and before-threshold fluctuations have been defined. References 4, tables 2, figures 5.